2017
DOI: 10.1186/s12877-016-0396-x
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and primary care obesity management in rural areas – innovative approach for older adults?

Abstract: BackgroundThe growing prevalence of obesity is paralleling a rise in the older adult population creating an increased risk of functional impairment, nursing home placement and early mortality. The Centers for Medicare and Medicaid recognized the importance of treating obesity and instituted a benefit in primary care settings to encourage intensive behavioral therapy in beneficiaries by primary care clinicians. This benefit covers frequent, brief, clinic visits designed to address older adult obesity.Discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 104 publications
1
49
0
Order By: Relevance
“…By identifying and including additional recent trials with GDM only, the understanding of TM management of GDM was updated and more significant differences in maternal and neonatal/foetal complications were confirmed, which could provide scientific guidelines for future TM management. The greatest potential of TM lies in its ability to help patients who cannot be easily treated at existing clinics due to geographical constraints [50,51].TM provides a convenient channel for communication between medical staff and patients, where medical staff could monitor the health status of patients in realtime, allowing patients to obtain individual treatment plans and disease-related knowledge of their own conditions, which may greatly improve the compliance of patients and further contribute to lower glycaemic levels [4,14]. Some studies have shown that the psychological status of pregnant women also has a certain impact on pregnancy outcomes [52].…”
Section: Discussionmentioning
confidence: 99%
“…By identifying and including additional recent trials with GDM only, the understanding of TM management of GDM was updated and more significant differences in maternal and neonatal/foetal complications were confirmed, which could provide scientific guidelines for future TM management. The greatest potential of TM lies in its ability to help patients who cannot be easily treated at existing clinics due to geographical constraints [50,51].TM provides a convenient channel for communication between medical staff and patients, where medical staff could monitor the health status of patients in realtime, allowing patients to obtain individual treatment plans and disease-related knowledge of their own conditions, which may greatly improve the compliance of patients and further contribute to lower glycaemic levels [4,14]. Some studies have shown that the psychological status of pregnant women also has a certain impact on pregnancy outcomes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been successfully applied in some medical professions and can be used as a useful way to provide much-needed intensive behavioral therapy in remote and resource-poor environment [9]. The way of applying telemedicine to serve patients' mental health can widen the channels of seeking medical treatment for elderly patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Because effective obesity interventions often require frequent contact with health care providers, telehealth serves as an effective way of following up with patients at short intervals. 3 A broad range of telehealth obesity-related interventions have been tried ranging from web-based learning modules, texts and smartphone applications, and wearable devices with varying degrees of success. 4,5 Malnutrition A recent systematic review showed that telehealth interventions (predominantly telephone consultations with dietitians) were effective and likely to result in clinical improvements in older adults with malnutrition.…”
Section: Obesitymentioning
confidence: 99%